2004
DOI: 10.1097/00000478-200402000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of JAZF1-JJAZ1 Gene Fusion in Endometrial Stromal Neoplasms with Classic and Variant Histology

Abstract: Endometrial stromal tumors (ESTs), including low-grade endometrial stromal sarcomas (LGESSs) and endometrial stromal nodules (ESNs) of classic histology, exhibit characteristic morphologic features and contain the nonrandom t(7;17)(p15; q21), which results in the fusion of two novel genes, JAZF1 and JJAZ1. ESTs may pose diagnostic challenges when they involve extrauterine sites, present as metastases, or display variant histologic appearances. The aim of this study was to evaluate the frequency of the JAZF1-JJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
105
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(117 citation statements)
references
References 41 publications
10
105
2
Order By: Relevance
“…2 Our results showing a high prevalence of JAZF1-JJAZ1 among endometrial stromal nodules (66%) are consistent with the several reports dealing with endometrial stromal nodule cases. Regarding endometrial stromal nodule, JAZF1-JJAZ1 gene fusion was detected in all three cases reported by Koontz et al,20 in the two cases reported by Huang et al, 31 and in all four cases reported by Nucci et al 28 As for endometrial stromal tumors with sex cordlike differentiation, there have been two cases reported in the literature in which JAZF1-JJAZ1 fusion was detected. 29,30 In our study, one of the two cases of endometrial stromal nodule with sex cordlike differentiation was positive for the JAZF1-JJAZ1 fusion transcript, supporting the idea that genetic heterogeneity exists among endometrial stromal tumors with variant histology.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…2 Our results showing a high prevalence of JAZF1-JJAZ1 among endometrial stromal nodules (66%) are consistent with the several reports dealing with endometrial stromal nodule cases. Regarding endometrial stromal nodule, JAZF1-JJAZ1 gene fusion was detected in all three cases reported by Koontz et al,20 in the two cases reported by Huang et al, 31 and in all four cases reported by Nucci et al 28 As for endometrial stromal tumors with sex cordlike differentiation, there have been two cases reported in the literature in which JAZF1-JJAZ1 fusion was detected. 29,30 In our study, one of the two cases of endometrial stromal nodule with sex cordlike differentiation was positive for the JAZF1-JJAZ1 fusion transcript, supporting the idea that genetic heterogeneity exists among endometrial stromal tumors with variant histology.…”
Section: Discussionmentioning
confidence: 84%
“…29,30 In our study, one of the two cases of endometrial stromal nodule with sex cordlike differentiation was positive for the JAZF1-JJAZ1 fusion transcript, supporting the idea that genetic heterogeneity exists among endometrial stromal tumors with variant histology. 31 On the basis of review of the literature and our study, we have hypothesized a simplified model for the histogenesis of endometrial stromal tumors and related high-grade sarcomas (Figure 4). It is commonly accepted that endometrial stromal nodule and low-grade endometrial stromal sarcoma belong to the same category featuring endometrial stromal differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The most common genetic aberration identified in ESNs, which is similarly identified in LGESS (discussed later), is t(7;17)(p15;q21). [9][10][11][12] Recognition as an Endometrial Stromal Neoplasm (Biopsy/Curettage Specimen)…”
Section: Endometrial Stromal Nodulementioning
confidence: 99%
“…29 The most common genetic abnormality in low-grade ESS is t(7;17)(p15;q21), resulting in the fusion of JAZF1 and SUZ12(JJAZ1) genes at 7p15 and 17q21, respectively. [9][10][11][12]30,31 The reported frequency of JAZF1-JJAZ1 fusion has been detected in~48% of low-grade ESS. 32 The second most frequent abnormality is t(6;7)(p21;p15), a so-called variant translocation of the t(7;17), because of the involvement of 7p15 and 6p21 instead of 17q21 resulting in a JAZF1-PHF1 fusion gene.…”
Section: Endometrial Stromal Sarcoma Low Gradementioning
confidence: 99%
“…[4][5][6][7] Low-grade endometrial stromal sarcoma is also characterized by chromosomal translocations in a subset of cases, most commonly t(7;17)(p15;q21) involving zincfinger genes, JAZF1 and SUZ1. [8][9][10][11][12][13][14] The WHO identifies undifferentiated endometrial sarcoma as displaying marked cellular atypia and lacking morphologic evidence of an endometrial stromal phenotype. Older grading systems, however, allowed for a category of endometrial sarcomas with greater atypia than low-grade endometrial stromal sarcoma, whereas retaining some resemblance to endometrial stroma.…”
mentioning
confidence: 99%